KINERJA KEUANGAN PT. UNILEVER INDONESIA,TBK DI BEI MENURUT RASIO LIKUIDITAS DAN RASIO SOLVABILITAS - MEGA ASTIKA, SITTI AULIA; RATNA SARI, A.; ISMAIL, ISMAIL (Patria Artha University, 2025)
This study aims to determine and analyze the financial performance of PT. Unilever Indonesia Tbk using financial aspects, namely the liquidity ratio consisting of the current ratio, cash ratio and quick ratio. The solvency ratio consists of the Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER). This study uses a quantitative descriptive method with a quantitative approach collected from the financial statements of PT. Unilever Indonesia Tbk for five periods from 2019 to 2023. The results of the study show that PT Unilever Indonesia Tbk from 2019 to 2023 has poor financial performance. The analysis shows that the company faces difficulties in paying off short-term liabilities because its liquidity ratio is below the industry standard. The cash ratio increased in 2023, but its value remained low. In terms of solvency ratios, the debt to assets and debt to equity ratios indicate a high dependence on debt.